Ecopedagogy through Makassar Paddy Mantras: A Model for Character Education and Environment Literacy - Yusmah, Yusmah; Supriadi, Supriadi; Kurniawan, Eri; Syahban Amir, Ali (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This article aims to explore the potential of paddy mantras from the Makassar community as a culturally embedded learning resource within the framework of ecopedagogy. Method: Employing a qualitative approach through field observation and documentation, this study reveals that paddy mantras contain ecological, spiritual, and social values that are highly relevant to the character development of primary school students. Results: Findings indicate that the integration of local texts not only enhances students’ ecological awareness and character formation but also strengthens cultural identity and collaborative spirit within the school environment, particularly at Inpres Ko’mara 1 Elementary School. Thus, tradition-based teaching serves as a strategic step toward achieving contextualized, character-oriented, and environmentally conscious primary education. and Novelty. Novelty: The unique contribution of this study lies in the integration of traditional paddy mantras into modern educational practices through innovative methods, such as mini planting projects, visual reflections, and the creation of local vocabulary booklets. Furthermore, the study bridges these local wisdom values with the dimensions of moral knowing as conceptualized by Lickona (1991), including perspective-taking, moral reasoning, decision-making, and self-knowledg thereby offering a novel model of ecopedagogical application in elementary education.